2020
DOI: 10.1155/2020/3056305
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Decisions and Coordination under the Combined Effect of Overconfidence and Fairness Concern

Abstract: The purpose of this study was to examine the joint effect of overconfidence and fairness concern on supply chain decisions and design contracts to achieve a win-win situation within the supply chain. For this study, a centralized supply chain model was established without considering the retailers’ overconfidence and fairness concern. Furthermore, the retailers’ overconfidence and fairness concerns were introduced into the decentralized supply chain, while the Stackelberg game model between the manufacturer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, in low-carbon supply chains, overconfidence can also affect the amount of money firms invest in R&D for emission reduction. Studies by Liu [47] and Lu [48] et al concluded that overconfidence can lead to greener, low-carbon products, but at the same time can lead to higher costs and less profitability for firms [42]. This paper constructs a supply chain system with one retailer and one manufacturer and introduces the behavioral characteristics of manufacturer overconfidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in low-carbon supply chains, overconfidence can also affect the amount of money firms invest in R&D for emission reduction. Studies by Liu [47] and Lu [48] et al concluded that overconfidence can lead to greener, low-carbon products, but at the same time can lead to higher costs and less profitability for firms [42]. This paper constructs a supply chain system with one retailer and one manufacturer and introduces the behavioral characteristics of manufacturer overconfidence.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also examine the impact of the interaction effect of overconfidence and social preferences on supply chains. Examples include discussing the interaction effect of overconfidence with equity concerns [40][41][42] and risk aversion [43] on supply chain performance. The second strand of literature examines the impact of overconfidence on supply chain coordination.…”
Section: Overconfidencementioning
confidence: 99%
“…Xiao et al [43] designed different types of optimal contracts to study the interactive impact of fairness and overconfidence in a two-echelon SC. Zhijian et al [49] also analyzed the combined effect of overconfidence and fairness on wholesale price, sales price, sales effort, and expected profits under demand uncertainty.…”
Section: Fairness and Overconfidence Behaviour Simultaneouslymentioning
confidence: 99%
“…As an outcome, the retailer reduced his order quantity and increased retail price because of the belief that P&G is unfair in sharing the profit [28]. In the literature, though the effects of fairness concern [36], and overconfidence behaviour [24] on SCs have been studied separately, there are scanty investigations [43,49] with the combined effect of the above two characteristics of SC members. In the context of the above available literature, the following research questions arise: (a) What will be the pricing strategy in an SC when substitute bundles are sold at the manufacturers' level?…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [39] studied a dynamic price game model in a dual-channel green supply chain and focused on the efect of parameter changes on the pricing strategies and complexity of the dynamic system in a dynamic environment. Zhijian et al [40] examined the joint efect of overconfdence and fairness concern on supply chain decisions and designed a buyback contract to coordinate the supply chain. Zhao et al [41] studied the pricing and coordination of green supply chains under capital constraints.…”
Section: Green Investment and Coordination In Supply Chainmentioning
confidence: 99%